Detection of Plasma Membrane Alpha Enolase (ENO1) and Its Relationship with Sperm Quality of Bali Cattle - T. Sumarsono; I. Supriatna; M. A. Setiadi; M. Agil; B. Purwantara (Tropical Animal Science Journal, 2023)
Bali cattle are the indigenous cattle well known attributed to their high fertility. Various proteomes in sperm are substances that can determine sperm quality and fertility. One of which is alpha enolase (ENO1). This study aims to assess the presence of ENO1 in the plasma membrane of sperm and its relationship with the semen quality of Bali cattle. The study used 30 ejaculates from 5 bulls for sperm quality assessment and detection of ENO1. Sperm quality is indicated by total motility, progressive motility, kinematics motility, viability, plasma membrane integrity, and ENO1 quantity. Sperm motility and kinematics motility were measured using CASA, while viability was assessed by eosin-nigrosine differential staining. The HOS test was used to determine plasma membrane integrity, and ENO1 quantity was measured by the ELISA method. Data were analyzed using ANOVA (randomized group design), linear regression, Pearson’s correction, and the t-Student test. The results showed that ENO1 was detected in the plasma membrane at 1.27 ng/106 sperms. The amount of alpha-enolase in the plasma membrane of Bali cattle sperm is affected by sperm concentration (p<0.01) and not involved in sperm motility. There was no correlation between plasma membrane ENO1 quantity and semen quality. The results of this experiment indicated that alpha-enolase in the plasma membrane of Bali cattle sperm is affected by sperm concentration but not related to sperm quality.